Corporate food donations: altruism, strategy or cost saving?. Issue 7 (17th July 2018) - Sert, Sedef; Garrone, Paola; Melacini, Marco; Perego, Alessandro
Abstract : Purpose: The purpose of this paper is to enhance the understanding of motives behind corporate giving and at finding out whether and when operational efficiency plays a major role in the case of surplus food donations by food supply chain companies. Design/methodology/approach: A multiple case study methodology has been applied considering a sample of 16 food sector companies operating in Italy. Three cases have been analyzed in-depth to highlight the contextual factors that make cost savings possible and donations sizeable and regular. Findings: The results show that the willingness of companies to reduce operational costs plays a relevant role in managerial decisions concerning the recovery and donation of unsold food, although to different degrees across the supply chain stages. Originality/value: The paper shows that not only strategic and moral motives, but also economic efficiency concern plays an important role in the managerial decision-making process pertaining to surplus food donations.